HGG-45. PROTEOMIC ANALYSIS OF PEDIATRIC DIFFUSE ASTROCYTOMAS YIELDS PATHWAYS ASSOCIATED WITH BOTH PROGRESSION-FREE AND OVERALL SURVIVAL. (4th December 2020) - Sells, Blake; Fleming, Jessica; Graham, Richard; McElroy, Joseph; Haque, Jahar; Boué, Daniel; Becker, Aline; Bell, Erica; Finlay, Jonathan; Chakravarti, Arnab
Abstract: Brain tumors are now responsible for more deaths each year than any other childhood cancer. Current studies aim to discover key molecular drivers that can explain prognosis and serve as targets for new therapeutic approaches, reducing morbidity. In this study, we performed LC-MS/MS proteomics on a cohort of 28 primary diffuse astrocytoma formalin-fixed paraffin embedded samples (WHO Grades II-IV) from patients at Nationwide Children's Hospital with a median follow-up time of 2.3 (0.6–20.2) years. Ingenuity Pathway Analysis was used to analyze the proteomic data after using both age and grade as covariates and only including proteins with p-values less than 0.05. The upregulation of a well-known oncogenic pathway, the Protein Kinase A signaling pathway, was significantly associated with greater risk of progression and death (P=5.5E-07 and P=4.6E-04). Integrin signaling, a pathway commonly suppressed in cancer, was similarly downregulated in those with greater risk of progression and death (P=3.3E-04 and P=1.7E-07). A global upstream analysis of the proteomic data also predicted activation of the oncogene MYCN in those who performed poorly, supporting previous studies. When comparing grade II (n=10) to grade III (n=8) and IV (n=10) primary tumors, the pathway most upregulated in higher histopathological grades was EIF2 Signaling (P=4.9E-49). This pathway has previously been associated with resistance in adult glioblastoma. These pathways, and the proteins detected within, may provide novel means by which to better understand and treat pediatric diffuse gliomas. Ongoing studies are in progress to understand how these pathways drive aggressiveness and differ from adult astrocytomas.